Psychological distress in mothers of infants admitted in neonatal intensive care unit (NICU) - Dr Niranjan HS; Dr Nijaguna A; Dr Jagadish AS; Dr Naveen Benakappa (Pediatric Review: International Journal of Pediatric Research, 2015)
Introduction: Mothers whose infants are admitted to NICU undergo significant distress which can interfere with mother infant bonding.Materials & Methods: Mothers belonging to two groups: Group 1 –(clinical) 30 mothers of infants admitted in NICU of IGICH. Group 2-(control) 30 mothers of normal infants from Jayanagar General Hospital (JGH) were included.Period Of Study: July 14 to Dec 14. All mothers cooperative for interview, mothers from intact families were included. Mothers of infants having major illness were excluded.Results: Qualitative analysis of clinical sample indicates 90% mothers in “extremely stressful” severity rating and 10% “very stressful” rating. Urban families experience more stress (p=0.012). Previous NICU experience showed higher stress levels as compared to no previous experience (p=0.052). Coping styles like praying to god about infant well being(100%), reading books(26%), always thinking about baby(100%), expressing emotions to husband and families (85%), blaming themselves(56%) and others like in laws(10%), meditating(12%), keeping feelings and emotions to themselves (43%), sitting and crying(10%). Control group used praying and talking to themselves (43%), sitting and crying (10%). Control group used praying and talking to family and coped better. Statistically significant difference indicating higher distress in mothers of clinical group.100% felt bad, lonely, hurt and sad, 50% felt hopeless about future and 25% expressed anger mostly directed towards their mother/husband. 70% mothers in clinical group were not allowed to breastfeed thus causing emotional distress to the mother.Conclusion: Mothers are at immense stress when separated from their infants hence measures to reduce the same must be considered.